2016
DOI: 10.3390/ma9010045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rare Earth Metals on the Microstructure of Al-Si Based Alloys

Abstract: The present study was performed on A356 alloy [Al-7 wt %Si 0.0.35 wt %Mg]. To that La and Ce were added individually or combined up to 1.5 wt % each. The results show that these rare earth elements affect only the alloy melting temperature with no marked change in the temperature of Al-Si eutectic precipitation. Additionally, rare earth metals have no modification effect up to 1.5 wt %. In addition, La and Ce tend to react with Sr leading to modification degradation. In order to achieve noticeable modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Figures 3 and 4 demonstrate the e ect of adding a relatively large amount of RE metals (without or with 0.15%Ti) to both base alloys. Based on these gures, it is clear that these additions resulted in As reported previously by the present authors [3,17], the observed depression in the eutectic temperature due to addition of RE metals is not necessarily related to modi cation of the eutectic Si particles as shown in Figure 5. It should be mentioned that only La revealed partial modi cation but was not as e ective a modi er as Sr in the Sr-treated alloys.…”
Section: Resultssupporting
confidence: 83%
“…Figures 3 and 4 demonstrate the e ect of adding a relatively large amount of RE metals (without or with 0.15%Ti) to both base alloys. Based on these gures, it is clear that these additions resulted in As reported previously by the present authors [3,17], the observed depression in the eutectic temperature due to addition of RE metals is not necessarily related to modi cation of the eutectic Si particles as shown in Figure 5. It should be mentioned that only La revealed partial modi cation but was not as e ective a modi er as Sr in the Sr-treated alloys.…”
Section: Resultssupporting
confidence: 83%
“…There are examples with an application of mischmetal and individual elements with positive effects, no effects [89], and detrimental influence on properties of aluminum alloys [90]. Rare earth elements such as La, Ce, Nd, and Y were tested with the Al−Si matrix [91]; Er with Al−Mg, Al−Zn−Mg, Al−Zn−Mg−Cu, Al−Li, and Al−Cu grades [92]; or Sm with Al−Si−Cu grades [93]. Among rare earths, cerium and scandium are of particular interest for aluminum alloying, as emphasized in [94][95][96].…”
Section: Rare Earth Metals In Aluminum Alloysmentioning
confidence: 99%
“…In addition, some researchers have studied the interaction between rare earth elements and commercial modifier Sr in Al melts. Alkahtani et al [27] studied the effects of La and Ce additions on the structure and properties of an A356 alloy containing Sr. The experimental results showed that La and Ce tended to react with Sr and resulted in fading of the modification effect of the Sr.…”
Section: Introductionmentioning
confidence: 99%